2019
DOI: 10.3390/rs11212478
|View full text |Cite
|
Sign up to set email alerts
|

Remotely-Observed Early Spring Warming in the Southwestern Yellow Sea Due to Weakened Winter Monsoon

Abstract: The seasonal warming over the southwestern Yellow Sea (YS) in the spring is of vital importance to the local ecologic environment, especially to the massive green algae blooms of the YS in late spring and early summer. Based on daily optimum interpolation sea surface temperature (SST) data consisting of satellite derived SST from Advanced Very High Resolution Radiometer (AVHRR) and in situ measurements, this study analyzed the spring SST variation over the southwestern YS (SWYS) from 1982 to 2018. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Over the land, the trends in wind speeds are weak in all the seasons. Earlier studies reported that southwesterly winds during SWM and northeasterly winds during NEM give rise to decreasing trends over the eastern Arabian Sea (Yu et al ., 2004; Bollasina et al ., 2011; Jaswal and Koppar, 2013; Miao et al ., 2017; Parvathi et al ., 2017; Swapna et al ., 2017; Wu et al ., 2019; Zhang et al ., 2019; Kumari et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Over the land, the trends in wind speeds are weak in all the seasons. Earlier studies reported that southwesterly winds during SWM and northeasterly winds during NEM give rise to decreasing trends over the eastern Arabian Sea (Yu et al ., 2004; Bollasina et al ., 2011; Jaswal and Koppar, 2013; Miao et al ., 2017; Parvathi et al ., 2017; Swapna et al ., 2017; Wu et al ., 2019; Zhang et al ., 2019; Kumari et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In order to analyze the timing of temperature change according to the change in wind and transport, the decadal variation of the three variables (Wind stress curl, Transport of Mid-ES, Subsurface temperature anomaly between 100 and 300 m depth) was examined. As air-sea interactions occur across all spatial and timescales (Wu et al, 2019), here our focus is on the interannual or decadal component of variations in air-sea interactions. In Region A, the decadal wind stress curl variation turned from a positive phase to a negative phase in the late 1990s (Figure 6A).…”
Section: Mechanism Underlying Surface Warming Slowdownmentioning
confidence: 99%
“…The application of remote sensing techniques is useful to coastal research [36,[79][80][81], the development of satellite techniques enables their use in different types of coasts. Most studies have focussed on determining and measuring trends of change [3,5,[9][10][11][12][13][14][15][16]. This study aimed to evaluate the suitability of airborne bathymetry LiDAR in determining the factors causing coastal degradation, by combining topographic and bathymetric data.…”
Section: Discussionmentioning
confidence: 99%
“…Global average temperatures are gradually increasing: this has far-reaching social and environmental consequences [1][2][3]. Mitigating the adverse impacts of climate change can reduce the global financial and social risks it poses.…”
Section: Introductionmentioning
confidence: 99%